O2-S6.04 An exploratory survey of male sex workers and HIV risk in an urban area of Southwest China. (10th July 2011) - Yu, B N; Wang, X A; Yu, F; Wang, J; Blanchard, J
Abstract : Background: Little knowledge is available on risk behaviours of HIV and basic demographic characteristics in male sex workers (MSW) in the population of men who have sex with men (MSM) in China. The objective of this study is to explore the risk to HIV/STI of MSW in southwest China through a convenience sample of an HIV surveillance survey of MSM. Method: Those who self-reported had been paid for sex or "engaging in money exchange for sex" were identified as MSW or "Money Boys". Data of the past five cycles (2004–2008) of an HIV surveillance survey were included in this study. Descriptive statistics were employed to describe demographics, sex practices, and HIV prevalence in these male sex workers. Results: A total of 117 men self-identified as MSW in five consecutive cross-sectional surveys (2004 n=54, 2005 n=39, 2006 n=45, 2007 n=34, and 2008 n=45). The median age of participants ranged from 25 to 27 years. In the 6 months prior to the survey, the median number of male sex partners ranged from 4 to 11; the median of number of female sex partners ranged from 0 to 2; over 90% (89%–98%) of MSW reported anal sex and 26% of them engaged in group sex; but proportions who reported always using condoms for anal sex were less than 60% (ranged from 28% to 60%). HIV screening positive rate was 9% in both 2007 and 2008 see Abstract O2-S6.04 table 1 . HIV positive rate is associated with the number of male sex partners and condom use frequency in both 2007 and 2008. Conclusion: MSW have been emerging in the sex trade industry in China. Behavioural risk factors and high prevalence of HIV in the MSW survey sample signalled a need for further understanding of this special population. Effective public health intervention strategy and programs are in urgent demand.